P142 Using the "spotting the signs" proforma in a gum clinic to facilitate identification of child safeguarding concerns. (18th May 2015) - Pye, Joanne; Gupta, Nadi
Abstract : Background/introduction: In the wake of recent events regarding child sexual exploitation, BASHH produced the 'Spotting the Signs' guidance. Our GUM department has been using the 'Spotting the Signs' proforma since August 2014 for all under 16 year olds routinely and any patients aged 16–17 where concerns identified. Aim(s)/objectives: The aim of this project was to review the data gathered using the proforma and review the number of safeguarding referrals made. Methods: All under 16s and any patients aged 16–17 seen between August and December 2014 were identified. A retrospective case note review was undertaken of all the proformas. Data gathered included non-consensual sex, age differences, drug and alcohol issues, coercion and number of referrals to child safeguarding. Results: 20 patients were identified (16 female, 4 male); 18 cases were under 16 years. Two patients aged 16–17 had been assessed using the proforma. 50% of patients were identified as having mental health issues, 55% were identified with concerns regarding exploitation and 20% were noted to have problematic drug/alcohol use. 55% of patients were referred to safeguarding services. Discussion/conclusion: Use of the proforma has increased identification of mental health issues, highlighted concerns regarding age differences and provided details of drug/alcohol use, social circumstances and sexual exploitation. The data suggests that use of the proforma allows a more detailed risk assessment thereby increasing the likelihood of identifying safeguarding issues. We initially used the proforma routinely in all under 16 year olds and have since expanded this to all under 18 year olds.